Development of an AAV DNA-based synthetic vector for the potential gene therapy of hemophilia in children - Shoti, Jakob; Qing, Keyun; Srivastava, Arun (Frontiers in Microbiology, 2022)
Recombinant AAV serotype vectors and their variants have been or are currently being used for gene therapy for hemophilia in several Phases I/II/III clinical trials in humans. However, none of these trials have included children with hemophilia since the traditional liver-directed AAV gene therapy will not work in these patients because of the following reasons: (i) Up until age 10-12, the liver is still growing and dividing, and with every cell division, the AAV vector genomes will be diluted out due to their episomal nature; and (ii) Repeated gene delivery will be needed, but repeat dosing, even with an ideal AAV vector is not an option because of pre-existing antibodies to AAV vectors following the first administration. Here we describe the development of an optimized human Factor IX (hF.IX) gene expression cassette under the control of a human liver-specific transthyretin promoter covalently flanked by AAV inverted terminal repeats (ITRs) with no open ends (optNE-TTR-hF.IX), which mediated ~6-fold higher hF.IX levels than that from a linear TTR-hF.IX DNA construct in human hepatoma cells up to four-weeks post-transfection. In future studies, encapsidation of the optNE-TTR-hF.IX DNA in liver-targeted synthetic liposomes, may provide a viable approach for the potential gene therapy for hemophilia in children.